Bridge to transplantation with long-term mechanical assist device in adults after the Mustard procedure - Maly, Jiri; Netuka, Ivan; Besik, Josef; Dorazilova, Zora; Pirk, Jan; Szarszoi, Ondrej (The Journal of heart and lung transplantation, 2015)
BACKGROUND: There is limited clinical experience with bridging to transplant with a left ventricular assist device (VAD) in patients with previously palliated transposition of great arteries. METHODS: Five adult patients presenting with systemic right ventricular failure 30 years after a Mustard operation were implanted with a HeartMate II VAD. The implant was completed using standard procedures with only minor modifications to accommodate right ventricular cannulation. RESULTS: All 5 patients were men, with a mean age of 31.5 ± 1.8 years and a median time since Mustard operation of 30 (range 28 to 32) years. All patients had sternal closure on Post-operative Day (POD) 1, and 2 patients required additional re-operation for bleeding. One patient required temporary support of the non-systemic ventricle. The mean duration of VAD support was 284 ± 177 days; 3 patients underwent heart transplant and 2 died on PODs 502 and 34, respectively. Both deaths were due to progressive heart failure and pump thrombosis. Comorbidities, anatomy and mediastinal scarring did not preclude implantation and heart failure symptoms improved in all patients. CONCLUSIONS: With the increased prevalence of late post-Mustard heart failure, bridge to transplant with a VAD may be a suitable treatment option for patients who are severely ill.
Keywords: transposition; mužské pohlaví; Arterial Switch Operation; Heart Transplantation; Transposition of Great Vessels; Adult; Mustard; dysfunkce pravé srdeční komory; Ventricular Dysfunction, Right; congenital heart disease; VAD; transpozice velkých cév; Humans; Heart-Assist Devices; korekce transpozice velkých arterií; systemic right ventricle; podpůrné srdeční systémy; dospělí; transplantace srdce; lidé; Male; bridge to transplant